465PA phase IIIb open-label study of afatinib in EGFR TKI-naïve patients (pts) with EGFR mutation-positive (EGFRm+) NSCLC: Exploratory biomarker analysis. (24th November 2019) - Wang, J; Zhao, J; Bai, H; Wang, X; Wang, Y; Duan, J; Chen, H; Meng, S; Tian, Y; Huang, D C-L; Wu, Y-L
Abstract: Background: Afatinib has demonstrated efficacy and safety in pts with EGFRm+ NSCLC. We report a biomarker analysis of EGFR TKI-naïve pts with EGFRm+ NSCLC treated with afatinib in a Phase IIIb study. The analysis explored the effect of tumor mutation status on patient outcomes. Methods: Pts with EGFR TKI-naïve locally advanced/metastatic EGFRm+ NSCLC received 40 mg/day afatinib. Primary endpoint was incidence of serious adverse events (SAEs). Secondary endpoints included drug-related AEs (DRAEs). Progression-free survival (PFS) was a further endpoint. For biomarker analysis, DNA was extracted from peripheral blood samples and analyzed using an amplification refractory mutation system. Samples taken at baseline and regular intervals were analyzed for EGFR mutations; specified non-EGFR mutations were identified at baseline. Results: This analysis included 64 Chinese pts (female 70%; mean age 57 years; EGFR mutations: L858R 50%; Del19 42%). All pts had ≥1 DRAE, most commonly (all grades/≥3) diarrhea (98/14%) and rash/acne (grouped term; 81/8%). 15 pts (23%) had ≥1 SAE; 6 (9.4%) had drug-related SAEs. 58 pts (90.6%) showed disease control; including 39 (60.9%) with an objective response. At baseline, 19/42 pts analyzed (45%) had additional non-EGFR mutations; 17 progressed, 2 died. Median PFS was 8 months (mo), vs 12 mo for pts with EGFR-only mutations (HR 1.72; 95% CI 0.88, 3.36; p = 0.1054). At Visit 3, EGFR mutation status of 33/40 pts (83%) changed from positive to negative; 28 progressed, 5 died. Median PFS was 11 mo vs 6 mo for pts who remained EGFRm + (HR 1.25; 95% CI 0.47, 3.30; p = 0.6556). Conclusions: In this analysis, there were no unexpected safety findings. There was no significant difference in PFS between pts with additional non-EGFR mutations vs those with EGFR-only mutations. Median PFS was almost twice as long in pts who became EGFR-mutation negative compared with those who remained EGFRm + (non-significant). This analysis suggests afatinib has clinical benefit for pts regardless of type of initial EGFR mutation. Clinical trial identification: NCT01953913. Editorial acknowledgement: Medical writing assistance, supported financially by Boehringer Ingelheim, was provided by Beth de Klerk of GeoMed, an Ashfield company, part of UDG Healthcare plc. The authors acknowledge Nick Xue, of Boehringer Ingelheim (China) Investment Co., and Agnieszka Cseh, of Boehringer Ingelheim RCV GmbH & Co. KG, for their support in the development of this abstract. Legal entity responsible for the study: Boehringer Ingelheim. Funding: Boehringer Ingelheim. Disclosure: S. Meng: Full / Part-time employment: Boehringer Ingelheim. Y. Tian: Full / Part-time employment: Boehringer Ingelheim. D.C-L. Huang: Full / Part-time employment: Boehringer Ingelheim . Y-L. Wu: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Honoraria (self): Roche; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Boehringer Ingelheim; Honoraria (self): Pfizer; Honoraria (self): Eli Lilly; Honoraria (self): MDS; Honoraria (self): BMS. All other authors have declared no conflicts of interest.